Performance Analysis of Dual Axis Solar Tracker, Single Axis Solar Tracker and Fixed Array Configuration - Norbu, Karma (Bhutan Journal of Research and Development, 2023)
Solar energy has become popular source of renewable energy owing to its cheap electricity generation and relatively low construction cost. With integration of solar PV tracking system, the electricity generation has boomed in its operating lifetime. This paper present performance analysis of dual axis solar tracker, single axis solar tracker and fixed array configuration in terms of energy generation and efficiency. Three solar experimental setups are designed, fabricated and tested. The experiment was conducted in Thimphu (27.415647N, 89.621183E) and obtained power generation data from 15-21 of March 2022. The sun tracking and data logging is performed by Arduino Uno microcontroller. The data obtained is analyzed to obtain results using Microsoft excel.